2004
DOI: 10.1158/0008-5472.can-03-3047
|View full text |Cite
|
Sign up to set email alerts
|

A Potential Oncogenic Activity of Platelet-Derived Growth Factor D in Prostate Cancer Progression

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
104
0
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(109 citation statements)
references
References 33 publications
3
104
0
2
Order By: Relevance
“…It has been reported that PDGF-D signaling is frequently deregulated in human malignancies with up-regulated expression of PDGF-D in lung, prostate, renal, ovarian, and brain cancer (3,(9)(10)(11)(12)(13). These results suggest that PDGF-D plays important roles in the oncogenesis of several malignancies.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that PDGF-D signaling is frequently deregulated in human malignancies with up-regulated expression of PDGF-D in lung, prostate, renal, ovarian, and brain cancer (3,(9)(10)(11)(12)(13). These results suggest that PDGF-D plays important roles in the oncogenesis of several malignancies.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to PDGF-B, PDGF-D is important for cellular transformation and support of tumor development, probably due to exclusive or preferential signaling through PDGFR␤ (8,30). A similar function has been ascribed to the PDGFR␣ agonist PDGF-C (5,6).…”
Section: Discussionmentioning
confidence: 93%
“…In human cancers, PDGFD up-regulation has been documented for prostate, lung, renal, ovarian, brain, breast, and pancreatic cancers (31,32). However, the mechanisms underlying the effect of PDGF-DD on tumor growth are still largely unknown.…”
Section: Discussionmentioning
confidence: 99%